Enhanced removal of trace pesticides and alleviation of membrane fouling using hydrophobic-modified inorganic-organic hybrid flocculants in the flocculation-sedimentation-ultrafiltration process for surface water treatment. (1st February 2023) - Li, Yunyun; Wang, Yadong; Jin, Jin; Tian, Ziqi; Yang, Weiben; Graham, Nigel J.D.; Yang, Zhen
Highlights: Surface water containing pesticides was treated by FSUF process. Dosing the flocculant HOC-M effectively removed pesticides. Residual HOC-M in UF unit enhanced fouling (especially irreversible) reduction. Hydrophobic association between HOC-M and pesticides promoted pesticide removal. HOC-M exerted a stable hydrophilization modification effect on membrane surfaces. Abstract: Pesticide concentrations in surface water occasionally exceed regulated values due to seasonal events (rainy season in high intensity agricultural areas) or intermittent discharges (leakage, spillage, or other emergency events). The need to remove pesticide compounds in these situations poses a challenge for drinking water treatment plants (DWTPs). In this work, the performance of dosing hydrophobic-modified inorganic-organic hybrid flocculants (HOC-M; lower acute toxicity than corresponding metal salt coagulants; acceptable economic costs when M=Al or Fe; prepared in large-scale quantities), for the removal of four different pesticides (each initial concentration: 0.25 μg/L) from Yangtze River water, and in mitigating membrane fouling, by an integrated flocculation-sedimentation-ultrafiltration (FSUF) process, was evaluated over a period of 40 days; the FSUF is well-established in many DWTPs. The mechanisms underlying the treatment were unveiled by employing a combination of instrumental characterizations, chemical computations, material flow analyses, and statistical analyses. Efficient pesticide removal (80.3%∼94.3%) and membrane fouling reduction (26.6%∼37.3% and 28.3%∼57.6% for reversible and irreversible membrane resistance, respectively) in the FSUF process were achieved by dosing HOC-M, whereas conventional inorganic coagulants were substantially inferior for pesticide removal (< 50%) and displayed more severe fouling development. Hydrophobic association between the pesticides and the hydrophobic organic chain of HOC-M played a predominant role in the improvement in pesticide removal; coexisting particulate/colloid inorganic minerals and natural organic matter with HOC-M adsorbed on the surface, acting as floc building materials, provided sites for the indirect combination of pesticides into flocs. The observed fouling alleviation from dosing HOC-M was ascribed to both the pre-removal of fouling-causing materials in the flocculation-sedimentation prior to UF, and a stable hydrophilization modification effect of residual HOC-M in the UF unit. The latter effect resulted from a hydrophobic association between the PVDF substrate of the membranes and the hydrophobic organic chains of the HOC-M, causing the hydrophilic ends of the HOC-M to be exposed away from the membrane surface, thereby inhibiting foulant accumulation. This work has not only demonstrated the superior performance of dosing HOC-M in the FSUF process for trace pesticide removal in DWTPs, but also clarified the underlying mechanisms. Graphical abstract: Image, graphical abstract